Analisis Keamanan Siber dan Hukum: Studi Kasus Bjorka - Radika Hanny Syah; Muhammad Irwan Padli Nasution (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Technology has always been a powerful tool in advancing human civilization. It allows us to become more organized, efficient, and connected. Since the advent of the Internet, we have increasingly relied on electronic communications as a means of conducting business. Cybersecurity, which also includes authentication, non-repudiation, and accountability, is an effort to protect the confidentiality, integrity, and availability of information in cyberspace. The process of protecting computers, servers, mobile devices, electronic systems, networks, and data from malicious attacks falls under the category of cybersecurity. The following questions were used to evaluate the descriptive data in this paper, which uses a qualitative management approach: What triggers hackers to infiltrate Indonesia and how does the government respond to it? Keywords: cybersecurity, data privacy, cyber law